2020
DOI: 10.1111/josi.12390
|View full text |Cite
|
Sign up to set email alerts
|

Gender at Work Across Nations: Men and Women Working in Male‐Dominated and Female‐Dominated Occupations are Differentially Associated with Agency and Communion

Abstract: Occupational gender segregation is a worldwide phenomenon. Research from Western regions such as the United States and Europe shows that the observation of occupational gender segregation can perpetuate gender stereotypes (social role theory; men are ascribed agentic traits, whereas women are ascribed communal traits). However, predictions from social role theory have not been well-tested in non-Western nations. In a study with 1,918 participants from 10 nations systematically differing in gender inequality, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 79 publications
4
29
0
2
Order By: Relevance
“…On average, participants indicated that 68% (43%) of people working in agentic (communal) professions were men. However, as expected, we found that the perceived segregation of labor varied across countries, from M = 18.40 in Japan to M = 31.43 in Russia, which suggests that occupations had a more equal distribution of women and men in some countries than in others (for more details, see Froehlich, Olsson, Dorrough, & Martiny, 2020). To test H2, we aggregated the division of labor index at the country level.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…On average, participants indicated that 68% (43%) of people working in agentic (communal) professions were men. However, as expected, we found that the perceived segregation of labor varied across countries, from M = 18.40 in Japan to M = 31.43 in Russia, which suggests that occupations had a more equal distribution of women and men in some countries than in others (for more details, see Froehlich, Olsson, Dorrough, & Martiny, 2020). To test H2, we aggregated the division of labor index at the country level.…”
Section: Resultssupporting
confidence: 76%
“…On average, participants indicated that 68% (43%) of people working in agentic (communal) professions were men. However, as expected, we found F I G U R E 1 This figure presents an example illustration describing the punishment rule of the compensation/punishment game (i.e., if Player E transfers 10 Talers in the form of punishment to Player C, 30 Talers are deducted from Player C's account) that the perceived segregation of labor varied across countries, from M = 18.40 in Japan to M = 31.43 in Russia, which suggests that occupations had a more equal distribution of women and men in some countries than in others (for more details, seeFroehlich, Olsson, Dorrough, & Martiny, 2020). To test H2, we aggregated the division of labor index at the country level.…”
mentioning
confidence: 99%
“…Such interventions are needed because gender segregation in occupational participation may be prevalent in more than just Western countries. Across 12 different countries, Froehlich et al. (2020) found gender segregation in occupations: Following stereotypes, individuals rated male targets in masculine-stereotyped occupations as more agentic than communal, whereas female targets were rated as more communal than agentic.…”
Section: Discussionmentioning
confidence: 99%
“…Portraying a gay man in a highly male-dominated occupational role (truck driver) shifted his ascribed traits in a more masculine, less feminine direction compared with the traits ascribed to gay men in general and a gay man in a feminine role (hairdresser; Fingerhut & Peplau, 2006). In Froehlich et al’s (2020) 10-nation study, participants judged that persons in male-dominated occupations possess agentic traits (e.g., assertive, competitive) and that persons in female-dominated occupations possess communal traits (e.g., kind, warm), regardless of their sex. This primacy of role information also emerged in experiments in which participants were more influenced by individuals’ male- or female-dominated occupations than by pronouns that defined their sex (e.g., “he,” “his” or “she,” “hers”; Gustafsson Sendén et al, 2020).…”
Section: Stereotype Formationmentioning
confidence: 99%